Fraccionamiento y caracterización del material húmico en algunos suelos de sabana de la Orinoquia Colombiana - Andreux, F.; Becerra, S.P. de. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
This study deals with the organic-rich horizons of eight representative soils of the tropical savanna in "Las Gaviotas", Vichada, Colombia. The majority of the soils have a pedogenesis of the oxic type, with an ustic moisture regime on the high plair and an aquic moisture regime in the poorly or imperfectly drained lowland drainage ways (esteros). There is a striking contrast in the morphology and in the humus composition between this two ladnscapes. The climatic conditions on the high plain favor an active cycle of organic residues. Because of the good drainage conditions, the soil has long dry periods wich retard the plomerization of some of the humic precursors wich eventually can be leached during thee rainy periods and may have some influence upon the non oxides to a depth of 100 cm. The loss of organic matter is also intense on account of the burning of the grass vegetation particularly in the sandy soils in wich the formation of clay-humus complexes is more difficult. In the "esteros" hydromorphic conditions largely control the humus formation. There is intense biological humification where periods of saturation alternate with dry periods. Clay-humus complexes are slowly formed where saturated conditions predominate.